Characteristics of Sirah Nabawiyyah in Sundanese Region: Analysis of the Wawacan Riwayat of Prophet Muhammad - Abdurrohman, Irwan; Ramdani, Acep Dani; Mubarok, Muhamad Raihan Syahrul (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
Sirah Nabawiyyah is an important instrument for understanding Islamic teachings comprehensively. Because it documents the practices of practicing the Qur’an directly by the Prophet SAW. For this reason, scholars from the early generations paid more attention to the sirah nabawiyyah, to the point that a lot of literature appeared about it. However, each Sirah nabawiyyah literature has different characteristics according to the situation and conditions at the time it was written. This research will analyze the characteristics of the Sirah nabawiyyah manuscript